Spontaneous magnetostriction in the Gd-Y system: analysis of phase transformations - Beznosov, A. B.; Fertman, E. L.; Eremenko, V. V.; Pal-Val, P. P.; Popov, V. P.; Chebotayev, N. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The transformations of magnetic and lattice subsystems states of Gd100-xYx (x=0, 5.5, 7.5, 10.2)alloys have been studied at temperatures 5-370 K in magnetic fields up to 4 kOe. The temperature dependences of elastic modules, thermal expansion, low field magnetization and magnetic anisotropy parameters were obtained. The linear spontaneous striction DL(T)/L=xh2 was analized, and the effectiveorder parameters h and magnetostrictive parameters x were evaluated for the four magnetic phases (canted ferromagnetic, deforming ferromagnetic helix, ferromagnetic helix, and the ferromagnetic cone, respectively): xcf=2.2×10-5, xdh=- 5.3×10-5, xfh=7.1×10-5, xfc=1.4×10-3.